Localization and internationalization methodology of software for deaf and hard of hearing - Zajančkauskienė, Lina (Lietuvos matematikos rinkinys, 2011)
While developing software programmers usually think only about his aim, his result and there are always no thoughts that in future this software should be useful for people who live abroad or have some special needs. This is why this software is always been changed, modified in order to localize for special region. This article deals on how programmers should develop their programs to prepare them for localization in sign language (at this time – adapt the software for Lithuanian sign language).
Keywords: ICT; special needs education; information technology; sign language (LSL)